Gender and Identity Recognition in a Visually Lossless Encoded Image - Sipani, Aasish; Mundra, Nidhi; Komati, Pavani (International Journal of Computer Sciences and Engineering, 2014)
The last decades have experienced astounding growth in the use of images that has resulted in large repositories of images that have to be stored and transmitted, bringing new techniques and standards to compress such data sets efficiently. Lossless, or numerically lossless, methods commonly achieve moderate compression ratios, whereas lossy methods achieve higher compression ratios at the expense of image ï¬delity. Performing recognition algorithms on these compressed images require extraction of original image from the codestream. The goal of this research is to examine the feasibility of implementing gender recognition algorithm and identity recognition algorithm directly into JPEG2000 compressed domain avoiding inverse discrete wavelet transform (IDWT). Such an approach would consequently enable the use of compressed images in recognition purposes, thus reducing both computational time and storage requirements.